2007
DOI: 10.1590/s1807-59322007000600010
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Body Mass Index and Postural Balance

Abstract: Greve J, Alonso A, Bordini ACPG, Camanho, GL. Correlation between body mass index and postural balance. Clinics. 2007;62(6):717-20. OBJECTIVE:To evaluate the correlation between body mass index (BMI) and postural balance in unipodal support. METHOD: 40 males, age 26 ± 5 yrs, body mass 72.3 ± 11 kg, height 176 ± 6 cm and BMI 23.3 ± 3.2 kg/m 2 , were submitted to functional stability tests using the Biodex ® Balance System (stability evaluation protocol level 2, which allows an inclination of up to 20° in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
120
4
26

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(164 citation statements)
references
References 9 publications
14
120
4
26
Order By: Relevance
“…Significant alteration of these circumference and width dimensions of the females with posterior balance strategy might be responsible for adoption of aforementioned hip strategy instead of ankle strategy as both of these also contribute to peripheral increase of total body fat and weight. The previous literature [27,31,32] supports the poor balance with the significant increase in BMI confining to the obese category whereas in contrary to that, the mean BMI of posterior balance strategy female in our study falls within the overweight category. The higher percentage of body fat in Asians at lower BMI [33,34] as well as an increased prevalence of truncal fat, might be the reason behind the presentation of posterior type instead of ideal sagittal neutral balance strategy [35].…”
Section: Discussioncontrasting
confidence: 86%
“…Significant alteration of these circumference and width dimensions of the females with posterior balance strategy might be responsible for adoption of aforementioned hip strategy instead of ankle strategy as both of these also contribute to peripheral increase of total body fat and weight. The previous literature [27,31,32] supports the poor balance with the significant increase in BMI confining to the obese category whereas in contrary to that, the mean BMI of posterior balance strategy female in our study falls within the overweight category. The higher percentage of body fat in Asians at lower BMI [33,34] as well as an increased prevalence of truncal fat, might be the reason behind the presentation of posterior type instead of ideal sagittal neutral balance strategy [35].…”
Section: Discussioncontrasting
confidence: 86%
“…There are other factors that might also increase a risk of falling, for example, sarcopenia (muscle wasting) and dynapenia (muscular strength loss), have been observed in these populations, and this contributes to the deterioration in physical capacity (Baumgartner et al 1998;Cruz-Jentof et al 2010;Clark and Manini 2010;Visser 2011). The effect of obesity on balance control has been previously observed and described elsewhere (McGraw et al 2000;Maffiuletti et al 2005;Greve et al 2007;Teasdale et al 2007;Menegoni et al 2009;Handrigan et al 2010), and the original contribution of this study is the demonstration of the added effect of obesity on balance control in older women aged 65-80 years old. Furthermore, despite the observed differences in balance control, it is important to note that these individuals were living independently.…”
Section: Discussionmentioning
confidence: 84%
“…The current study showed significant relationships between body composition indexes and almost all stabilometric variables measured. Some authors also showed a positive correlation between body adiposity and body balance control 6,24 . Interestingly, almost one third of our participants had a BMI consistent with overweight or obesity; it is possible that fat accumulation and body mass increases can causes a center of pressure displacement, which can generate loss of stability mechanisms 6 .…”
Section: Discussionmentioning
confidence: 94%